Model Latihan Speed Endurance Berbasis Senam Pencak Silat Untuk Usia Remaja - Angga Septiadi; Hernawan Hernawan; Widiastuti Widiastuti (Journal Sport Area, 2019)
The purpose of research and development of pencak silat calisthenics training model for adolescents uses research method of Research & Development (R & D) from Borg and Gall. The subjects in this research and development are teenage athletes PPLP Riau Province, University of Pencak Silat Walet Puti Riau Province, University of Pencak Silat Tapak Suci Pekanbaru and Pencak Silat University of Kumango Riau Province. The test of model effectiveness uses test instrument to collect data of pencak silat athlete abilities. Analysis of research data uses the test of independent samples t-test with significance level of 0.05. Data analysis is obtained the average value of speed endurance training given the model of pencak silat calisthenics exercises in the experimental group is 478.94 and there are differences in results with the control group by the treatment with the common practice 431,23 test of difference significance with SPSS 17 gained result of t-count 2,396, df = 60 and p-value = 0.020 < 0.05. Based on the information, it can be concluded that the model of pencak silat calisthenics training for pencak silat athletes uses hand attacks developed and can be applied effectively and efficiently so it can improve the ability of pencak silat athletes.